The Effect of Using Paragraph Shrinking Strategy Toward Students Reading Comprehension in Narrative Text at Ninth Grade of MTS Koto Tinggi - Rara Vanesia; Reflinda Reflinda; Melyan Melani; Absharini Kardena (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted to determine the effect of using the paragraph reduction strategy on students' reading comprehension in Narrative Text in class nine at MTS Koto Tinggi. The background of this research is based on students' problems in reading comprehension when learning English. First, students cannot find the main idea and identify important information in the text. Second, students are lazy to read and understand texts because students do not know the meaning of the vocabulary in the text. Third, some students got low scores in reading. In this research, researchers used quantitative methods with a quasi-experimental research design by comparing two classes. The sample for this research was class 9 students at MTS Koto Tinggi, IX B as the experimental class, totaling 15 students, and IX C as the control class, totaling 15 students. The instrument of this research is a reading test. Data were analyzed using SPSS 22. The results showed that there was a significant influence on students' reading comprehension between students who were taught using the paragraph reduction strategy and without using the paragraph reduction strategy. This can be seen from the data calculations in the one sample t test and paired sample t-test showing a 2-Tailed significance of 0.000 < 0.05 so that Ha is accepted and Ho is rejected. It can be concluded that there is a significant effect of using the paragraph reduction strategy on students' reading comprehension and there is a difference between the reading comprehension of students taught using the paragraph reduction strategy and students taught using conventional methods. It can be concluded that the use of the paragraph reduction strategy has a significant influence on students to improve reading comprehension.